Experimental investigation of ternary blends on performance, and emission behaviors of a modified low-heat rejection CI engine - Ellappan, Sivakumar; Rajendran, Silambarasan; Dhairiyasamy, Ratchagaraja; Al-Mdallal, Qasem M; Khan, Sher Afghan; Asif, Mohammad; Dixit, Saurav; Ağbulut, Ümit (Elsevier, 2024)
This study investigated the performance, combustion, and emissions of a modified low-heat rejection (LHR) diesel engine fueled with a blend of 90 % coconut waste cooking oil (CWCO) biodiesel and 10 % diethyl ether (DEE). The engine combustion chamber components were coated with 300 μm lanthanum-doped partially stabilized zirconia for thermal insulation. Engine testing was performed at varied loads from 0 to 100 % using an eddy current dynamometer. Exhaust emissions, including hydrocarbons (HC), carbon monoxide (CO), nitrogen oxides (NOx), and smoke were measured. Compared to conventional diesel, the CWCO-DEE blend showed a 3 % higher brake thermal efficiency of 33.4 % and 2.42 % lower brake-specific fuel consumption at full load. HC, CO, and smoke emissions decreased by 18 % (39 ppm), 11 %, and 19 % at higher loads with the blend. However, NOx emissions increased slightly by 21.2 %. The DEE compensated for CWCO's lower cetane number and viscosity, while the LHR coating enhanced combustion by providing thermal insulation, raising exhaust gas temperatures by 13 %. The improved efficiency and reduced emissions demonstrate the potential of optimized biodiesel-additive blends in conjunction with LHR engine modifications to sustainably utilize inexpensive waste cooking oil feedstocks as renewable diesel replacements. However, further optimization of blend compositions, additives, and coatings is needed to balance performance benefits against possible NOx increases.